Język angielski w procesie uczenia się języka niemieckiego – pomoc czy przeszkoda? Krytyczna analiza ankiet przeprowadzonych wśród studentów anglistyki Uniwersytetu Śląskiego w grupach tłumaczeniowych z językiem niemieckim - Tobiasz, Lesław (Neofilolog, 2019)
The article presents results of an inquiry made among the students of English philology who learn German mostly as L3 in addition to English as L2 in a special translation program. The inquiry shows through many examples that English is a source both for complex positive transfer into German as well of interference. The answers of the students indicate the very important role of individual characteristics in the process of language learning. The author concludes that effective leaning of a foreign language requires the use of individual learner strategies and appropriate reference to knowledge both in the mother tongue and in other foreign languages.